소득작물 후작용 고품질 조생 벼품종 ‘화왕’ - 이종희(Jong-Hee Lee); 이지윤(Ji-Yoon Lee); 여운상(Un-Sang Yeo); 송유천(You-Chun Song); 박동수(Dong-Soo Park); 황운하(Un-Hwa Hwang); 박수권(Soo-Gwan Park); 박노봉(No-Bong Park); 김상열Sang-Yeol Kim; 오성환(Seong-Hwan Oh); 한상익(Sang-Ik Han); 남민희(Min-Hee Nam); et al. (Korean journal of breeding, 2018)
‘Hwawang’ is an early maturing and short statured rice cultivar adaptable to the rice–cash crop rotation system that was developed by the rice breeding team of the Department of Southern Crop, National Institute of Crop Science (NICS), Rural Development Administration (RDA), Korea, in 2012. This cultivar was derived from the cross of YR25867 (Hitomebore//YR21247-B-B-B-49-1/Sasanishiki BL4) and YR25866 (Akidagomachi//YR21247-B-B-B-49-1/Sasanishiki BL4) during the 2005/2006 winter season and was fixed as a homozygous line by a doubled haploid breeding system. In the replicated yield trial in 2009, a promising line (YR26253Acp26-1) showed a good phenotype and high yield potential, and so it was selected and designated as ‘Milyang256’. The local adaptability test of ‘Milyang256’ was carried out at three locations from 2010 to 2012. It was named ‘Hwawang’ and had a high head rice ratio and good eating quality. The culm length of ‘Hwawang’ averaged 62 cm during the yield trials and was 10 cm shorter than that of ‘Keumo’. The number of spikelets per panicle of ‘Hwawang’ was significantly lower than that of ‘Keumo’, but the number of tillers per hill was higher. This variety showed resistance to bacterial blight disease but was moderately susceptible to both leaf and neck blast. The milled rice yield of ‘Hwawang’ was 452 kg/10 a at the late transplanting stage of the local adaptability test. Thus, ‘Hwawang’ is well adapted to the rice–cash crop rotation system in the southern plain area. (Registration No. 5106) KCI Citation Count: 5